2022
DOI: 10.1136/bmjgh-2021-008162
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel determinants of community health workers for an effective maternal and child health programme in sub-Saharan Africa: a systematic review

Abstract: BackgroundCountries in sub-Saharan Africa (SSA) continue to have the highest maternal and under-five child deaths in the world. The ongoing COVID-19 pandemic is amplifying the problems and overwhelming already fragile health systems. Community health workers (CHWs) are increasingly being acknowledged as crucial members of the healthcare workforce in improving maternal and child health (MCH). However, evidence is limited on multilevel determinants of an effective CHWs programme using CHWs’ perspective. The obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 60 publications
0
24
0
Order By: Relevance
“…This upgrade simplifies CHWs’ work methods, thereby empowering them. This empowerment motivates CHWs, improves their abilities, and enhances work efficiency [ 56 ]. This empowerment is crucial for sustaining CHW programs and improving healthcare delivery in underserved areas.…”
Section: Discussionmentioning
confidence: 99%
“…This upgrade simplifies CHWs’ work methods, thereby empowering them. This empowerment motivates CHWs, improves their abilities, and enhances work efficiency [ 56 ]. This empowerment is crucial for sustaining CHW programs and improving healthcare delivery in underserved areas.…”
Section: Discussionmentioning
confidence: 99%
“…Our study was guided by different theoretical frameworks which informed the research processes and research questions. First, we used the socio-ecological model (SEM) to inform the description of the multilevel determinants of the CHWs program’s effectiveness [ 16 , 38 ]. The socio-ecological framework posits that factors at various levels uniquely and jointly contribute to health interventions.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The health program has overwhelmingly failed to address the quantity and quality of health workers [ 18 , 20 ]. The CHWs program continues to experience multiple challenges to enhance health outcomes [ 10 , 13 , 15 , 16 , 21 – 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, this present review has shown that CHWs can deliver a range of services for patients requiring physical rehabilitation services as long as training or orientation is given. The need for standardisation of training and integration is emphasized as there is evidence of CHWs' effectiveness in service delivery taking into consideration that there is a chronic shortage of human resources for health, especially in SSA countries [71].…”
Section: Implications For Practicementioning
confidence: 99%